PENGUJIAN MESIN EXTRUDER UNTUK PEMBUATAN FILAMEN BERBASIS SAMPAH PLASTIK - Sanndy Wahyu Nugroho (2020)
Plastics are material that is often found in people's lives because of its advantages. But it has a disadvantage, that is difficult to decompose naturally so that it can cause damage to ecosystems in the world. Therefore, plastics waste must be recycled. One of the plastics waste recycling machines is an extruder machine. The research is to find out the advanced specifications needed on the Extruder Machine so that the design of the spec applied is not excessive. The research methods are theoretical with calculations and simulations to determine whether or not the influence of screw rotating speed variations on the Volumetric Flow Rate (Q). The results of this research are the design of 3 cm diameter screw, 79 cm length, helix angle 19.05⁰, and screw rotating speed 100 rpm, produces Volumetric Flow Rate (Q) = 7.57647 x 10- 6 m3/s, Product Rate (Speed) = 27.4 m/min. The screw rotation speed are greatly affects the volumetric flow rate. The results tend to increase with the size of the screw rotation speed. Key words: Plastics Waste, Ecosystem Damage, Recycling, Extruder Machine.